Delamanid Central Nervous System Pharmacokinetics in Tuberculous Meningitis in Rabbits and Humans - Elizabeth W. Tucker; Lisa Pieterse; Matthew Zimmerman; Zarir Udwadia; Charles A. Peloquin; Maria Tarcela Gler; Shashank Ganatra; Jeffrey A. Tornheim; Prerna K. Chawla; Janice Caoili; Brittaney Ritchie; Sanjay K. Jain; et al. (2019)
Central nervous system tuberculosis (TB) is devastating and affects vulnerable populations. Multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculous meningitis (TBM) specifically are nearly uniformly fatal, with little information being available to guide the treatment of these patients. Delamanid (DLM), a nitro-dihydro-imidazooxazole, is a new, well-tolerated anti-TB drug with a low MIC (1 to 12 ng/ml) against Mycobacterium tuberculosis .